Prenylated cyclohexene-type meroterpenoids and sulfur-containing xanthones produced by Pseudopestalotiopsis theae. (May 2022) - Akone, Sergi Herve; Wang, Hao; Misse Mouelle, Eitel Ngoh; Mándi, Attila; Kurtán, Tibor; Koliye, Pierre Roger; Hartmann, Rudolf; Bhatia, Sanil; Yang, Jing; Müller, Werner E.G.; Lai, Daowan; Zhen Liu,; et al.
Abstract: Chemical investigation of the fungal endophyte Pseudopestalotiopsis theae isolated from leaves of Caloncoba welwitschii, collected in Cameroon, resulted in two previously undescribed sulfur-containing xanthone derivatives sydoxanthones D and E, in addition to three previously undescribed monomeric diisoprenyl-cyclohexene-type meroterpenoids biscognienynes D-F and five known natural products. The structures of the undescribed compounds were unambiguously identified by their mass spectra and by extensive 1D and 2D NMR spectroscopic analysis. Mosher's reaction was performed to determine the absolute configuration of sydoxanthones D and E while TDDFT-ECD calculations were used to assign the configuration of biscognienyne D. Biscognienynes B and D showed significant cytotoxicity against the mouse lymphoma cell line L5178Y with IC50 values of 7.7 and 6.7 μM and against the human leukemic cell lines HL60, and Hal-01 with IC50 values ranging from 4.3 to 12.1 μM. Graphical abstract: Image 1 Highlights: Sydoxanthone D and E were isolated from Pseudopestalotiopsis theae. Biscognienyne D-F were isolated from Pseudopestalotiopsis theae. ECD calculations and Mosher reaction were used for absolute configuration determination. Significant cytotoxicity displayed against several cell lines.